A Comparative analysis of SME internationalisation models between developed and developing countries - Ahmad, M O (2017)
There is a lack of extensive literature covering the contemporary trends observed in SMEs entering international markets, with the majority of the fundamental theories and concepts originating from models dated a few years back. The majority of the literature focuses on the trends and theories related to large Multinational enterprises (MNEs). Contemporary literature does offer new findings relating to internationalisation but these findings are not contextualised to SMEs specifically. There is also a significant gap in relating trends between firms from developed countries and developing ones. The limited literature which does so is specific to MNEs rather than SMEs. This study aims to fill such gaps and judge the validity of previous theories to a current sample. The sampling of 2 firms allows comparisons to also be made between firms originating from the developed world and the developing world as well as to the trends observed in the literature. High ranking mangers of both firms were interviewed and their responses interpreted to reflect the strategies adopted by each firm and the perceptions of the managers and the firms regarding internationalisation. The findings reflected certain inconsistencies within the literature. The UK based firm was classified as a ‘Born Global’ firm according to more contemporary theories. However, the Pakistani firm was more consistent with traditional literature opting for a low risk exporting strategy and exhibiting little to suggest eccentricity from the norm. The study was limited by its small sample and further research could aim to conduct similar research with a larger and broader sample. This study represents a positive step in filling significant gaps in the literature relating to SME internationalisation as well as identifying outdated theories and concepts which are misleading when applied in a current context.